The return of chloroquine-susceptible Plasmodium falciparum malaria in Zambia. (December 2016) - Mwanza, Sydney; Joshi, Sudhaunshu; Nambozi, Michael; Chileshe, Justin; Malunga, Phidelis; Kabuya, Jean-Bertin; Hachizovu, Sebastian; Manyando, Christine; Mulenga, Modest; Laufer, Miriam
Abstract Background Plasmodium falciparum resistance to anti-malarial drugs remains a major obstacle to malaria control and elimination. The parasite has developed resistance to every anti-malarial drug introduced for wide-scale treatment. However, the spread of resistance may be reversible. Malawi was the first country to discontinue chloroquine use due to widespread resistance. Within a decade of the removal of drug pressure, the molecular marker of chloroquine-resistant malaria had disappeared and the drug was shown to have excellent clinical efficacy. Many countries have observed decreases in the prevalence of chloroquine resistance with the discontinuation of chloroquine use. In Zambia, chloroquine was used as first-line treatment for uncomplicated malaria until treatment failures led the Ministry of Health to replace it with artemether-lumefantrine in 2003. Specimens from a recent study were analysed to evaluate prevalence of chloroquine-resistant malaria in Nchelenge district a decade after chloroquine use was discontinued. Methods Parasite DNA was extracted from dried blood spots collected by finger-prick in pregnant women who were enrolling in a clinical trial. The specimens underwent pyrosequencing to determine the genotype of theP. falciparum chloroquine resistance transporter, the gene that is associated with CQ resistance. Results Three-hundred and two specimens were successfully analysed. No chloroquine-resistant genotypes were detected. Conclusion The study found the disappearance of chloroquine-resistant malaria after the removal of chloroquine drug pressure. Chloroquine may have a role for malaria prevention or treatment in Zambia and throughout the region in the future.